BUSINESS EXPANSION: A LITERATURE REVIEW ON FRANCHISING AND BRAND LICENSING - Diego Weber dos Santos, Jean (Journal of Interdisciplinary Debates, 2026)
This article presents a literature review on business expansion strategies, with a special focus on the models of franchising and brand licensing. The analysis covers the main theories that support business expansion, including Agency Theory, Transaction Cost Theory, and the Uppsala Model of internationalization. The objective is to consolidate existing knowledge, identify the advantages and disadvantages of each model, and point out directions for future research. The review demonstrates that while franchising is a robust strategy for rapid market penetration and geographic growth with limited capital, brand licensing offers a flexible way to leverage brand value and intellectual property. The choice of the optimal strategy depends on a complex interaction between the company’s resources, market conditions, and long-term strategic objectives.